ANALISIS KONDISI RANTAI PASOK KOMODITAS KENTANG (SOLANUM TUBEROSUM L.) DI KABUPATEN BREBES - Khatimah, Khusnul (Universitas Sebelas Maret, 2023)
The potato is one of the vegetables comodities in Brebes Regency. The last three years, there has been a decline in production. Supply chain that has been implemented is deemed not optimal while the region has potential that can be exploited. The purpose of this study was to determine supply chain of the potato in Brebes Regency.The analytical method uses a Food Supply Chain Network (FSCN). The result showed that conditions based on the aspects of the target, structure, management, resources, and supply chain business processes. Target potatoes are sold to the local Brebes market and outside the region. There are four supply chain structure.It members are farmers, middlemen, wholesalers, small traders, retailers, and consumers. Supply chain management related to partner selection, contractual agreements, transaction systems, government support, and supply chain collaboration. The criteria for selecting partners are bidders with high prices, customers, and middlemen who are bound to provide capital loans to farmers. Transaction system through grace and cash system. The government support also contributes to the sustainability of it. Resources owned by members of the supply chain consist of physical, technology, and capital resources. Business processes can be seen from distribution patterns, support chain members, risk and trust building. Distribution patterns flow products, finance, and information from farmers to consumers, and vice versa. Each member of the potato supply chain requires equipment and input in the form of raw materials in the production process. Each member has different risks in the supply chain business process.